Persepsi Petani terhadap Program Upaya Khusus Peningkatan Produksi Padi, Jagung, dan Kedelai (Kasus Teknologi SRI di Subak Lungatad, Desa Peguyangan Kangin, Kecamatan Denpasar Utara, Kota Denpasar) - INDRATANAYA, I GEDE NGURAH SWARNA DWIJA; SUARDI, I DEWA PUTU OKA; DEWI, IDA AYU LISTIA (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism); Vol.8, No.2, April 2019, 2019)
Perception of Farmers on Special Efforts to Increase Rice, Corn and Soybean Production (The Case of SRI Technology in Subak Lungatad, Peguyangan Kangin Village, Denpasar City) The need for food is one of the main aspects for the survival of society. Special Food for food self-sufficiency 2015-2017 is the effort of the Ministry of Agriculture to succeed in self-sufficiency in rice, corn, soybeans in 2017. One of the hopes as the best solution for agriculture in Indonesia in increasing production is through a method of farming patterns with the System of Rice Intensification (SRI). The purpose of this study was to find out the perception of farmers on the Upsus Pajale program, especially SRI technology in Subak Lungatad, Peguyangan Kangin Village, North Denpasar District. The number of samples was 30 farmers. The data were gathered through questionnaires using quantitative and qualitative data types. The data that had been processed were further analyzed using qualitative descriptive analysis method. Research results show that the farmers' perceptions of SRI technology: (1) innovation was in good category with a score of 3.96, (2) social aspects were in good category with a score of 3.61, (3) economic aspects were in good category with a score of 4.09. And (4) the technical/ environmental aspects were also in the good category with a score of 3.48. Based on the results of the research and conclusions obtained, the suggestion that can be made to the government is that they should provide more input on the SRI planting system, both through technical guidance, field practice (making demonstration plots) and mentoring during each planting season, so that the results achieved could be railored to the expectations of all parties. It is also recommended that they should pay more attention to the rice sales system which is currently being sold using a slash system, with the calculation using the area (acre), thus making it difficult for farmers to obtain optimal benefits.